(untitled) (Iranian Journal of Kidney Diseases, 2019)
Sheehan syndrome (SS) is postpartum hypopituitarism resulting from pituitary gland necrosis caused by severe hypotension due to massive intra or post-partum hemorrhage. Defective NaCl transport in the distal convoluted tubule, due to mutations affecting the thiazide sensitive Na-Cl-cotransporter results in the autosomal recessive salt-losing renal tubulopathy, Gitelman syndrome (GS). These two have been rarely described together. We report the case of a middle-aged woman with both these conditions, resulting in management issues. Physicians encountering unexplained hypokalemia refractory to standard management must consider the possibility of renal tubular disorders.